(untitled) (Research, Society and Development, 2022)
This study aimed to verify the trends of organizational process modeling applied to public institutions in the international scenario. In this sense, a systematic review was elaborated, using the integrative method for search and analysis of articles published between 2010 and 2020 with the Scielo and Web of Science databases. After survey and filtering, we reached the number of ten papers examined, which bring different perspectives regarding methods, approaches, objectives, units of analysis and stages of modeling processes carried out in the studies. As results found, BPMN is focused as a widely used notation, often in conjunction with another type of notation, in order to cover the aspects considered for analysis and verification of processes, or to improve the results of public services provided. The use of information and communication technology (ICT) tools in this area was also corroborated in order to promote the interaction between the various actors of the processes modeled by digital means, considering intra, inter and extraorganizational relationships. As main results, co-production, involving citizens, as well as interorganizational co-governance, can be pointed out as emerging phenomena in modeling processes. Such involvements have been guaranteed by technology, such as the use of application systems.